Distillate water quality analysis and economics study of a passive solar still - Kumar, Ashish; Anthony, Prashant; Zaidi, Mohd. Asghar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> An experimental investigation on a double slope solar still is carried out to examine the quality of water under outdoor environment. Three synthetic water samples were prepared by adding Na2CO3, NaHCO3, CaCl2, and MgCl2. Few physical and chemical parameters were checked before and after the distillation namely: appearance, color, odor, pH, total alkalinity, total hardness and chloride content. It is found that the results agree with the standard values as prescribed by WHO and BIS-1991. Daily yield of the still is 3 L/m2/day. The payback period of the still is calculated and found to be 67 days which shows the utility of this solar still. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->